Newlywed Couples' Marital Adjustment - Pradipta, Mila; Prihanto, Sutyas (ANIMA Indonesian Psychological Journal, 2011)
Newlywed couple is a term for a couple of husband and wife who are just commencing into the marriage life. The first two years of marriage (newlywed) is a period of adjustment to the partner one has just been married to. This study aimed to assess marital adjustment in newlywed couples, which include the factors considered important in marital adjustment, the difference in the appraisal of the degree of importance between husbands’ and wives’, and the relationship between adjustment to marital satisfaction. This exploratory study involves 80 subjects (40 couples) from Surabaya, Malang, Jogjakarta, and Jakarta. This study showed that marital adjustment was based on the agreement established by the couples, enabling them to be integrated in expressing their hopes and feelings to each other to achieve marital satisfaction. Pasangan Newlywed adalah sebutan bagi pasangan suami istri yang baru memasuki kehidupan perkawinan. Dua tahun pertama perkawinan (newlywed) merupakan masa penyesuaian diri terhadap pasangan. Penelitian ini bertujuan mengaji penyesuaian perkawinan pada pasangan yang baru menikah, yang meliputi faktor-faktor yang dinilai penting dalam penyesuaian perka- winan, perbedaan nilai kepentingan antara pihak suami dan istri, dan keterkaitan antara penye- suaian dan kepuasan perkawinan. Penelitian deskriptif menyertakan 80 subjek (40 pasangan) dari Surabaya, Malang, Yogjakarta, dan Jakarta. Secara garis besar penelitian ini menunjukkan hasil bahwa penyesuaian perkawinan didasari oleh kesepakatan yang dibentuk oleh suami istri dan melalui kesepakatan tersebut akan terbangun keterpaduan dalam mengekspresikan harapan dan perasaan satu sama lain hingga tercapai kepuasan perkawinan.